KONSEP DASAR KEBERADAAN MASYARAKAT DAN TERBENTUKNYA INTEGRASI SOSIAL - Dewi, Oetami (Sosio Informa, 2007)
When I start to write this article, I believed that society could be existed while every actors has their relation with others actors, since this happened we could say that the society give many interaction, consensus among the others. Like what Karl Marx, Weber, Durkheim pointed in their research in many areas, I just want to point that we can’t avoid the conflict in every situation as conflict itselves bring many consensus among other actors. Functional Structural also said that in society it seems that conflict as an enemy, but in fact it’s not appear as to clear like conflict describe the situation. Regarding this article, I would like to persue the readers to know deeply about what is society, conflict and the reason why in every society has appeared conflict and why we need social integration. Key word : Social integration, conflict, society.